2017
DOI: 10.1097/aud.0000000000000496
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Spectral-Temporally Modulated Ripple Test With the Arizona Biomedical Institute Sentence Test in Cochlear Implant Users

Abstract: Objectives Although speech perception is the gold standard for measuring cochlear implant (CI) users’ performance, speech perception tests often require extensive adaptation to obtain accurate results, particularly after large changes in maps. Spectral ripple tests, which measure spectral resolution, are an alternate measure that has been shown to correlate with speech perception. A modified spectral ripple test, the spectral-temporally modulated ripple test (SMRT) has recently been developed, and the objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 26 publications
1
45
2
Order By: Relevance
“…A recently published pilot study of the DCF strategy (de Jong, Briaire, and Frijns 2018) showed there was better performance on the SMRT with DCF, especially at lower loudness levels. Because the SMRT correlates with speech understanding (Holden et al 2016;Lawler, Yu and Aronoff 2017;Zhou 2017), speech perception in noise was also expected to improve after some adaptation time. As the pilot study revealed a decrease in DCF battery life to 1.5-4 hours, some alterations to the fitting parameters were required to enhance clinical suitability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently published pilot study of the DCF strategy (de Jong, Briaire, and Frijns 2018) showed there was better performance on the SMRT with DCF, especially at lower loudness levels. Because the SMRT correlates with speech understanding (Holden et al 2016;Lawler, Yu and Aronoff 2017;Zhou 2017), speech perception in noise was also expected to improve after some adaptation time. As the pilot study revealed a decrease in DCF battery life to 1.5-4 hours, some alterations to the fitting parameters were required to enhance clinical suitability.…”
Section: Discussionmentioning
confidence: 99%
“…This was unexpected, as both psychophysical measures are known to correlate independently with speech understanding (Fu 2002;Holden et al 2016;Zhou 2017;Won et al 2007Won et al , 2013. The adaptation period of 5 weeks may not have been long enough to completely adjust to the novel strategy, so the final performance was still not reached (Lawler, Yu, and Aronoff 2017). This study intended to examine the effect of using the DCF strategy chronically; thus, an extra analysis was performed excluding subjects who did not use the strategy for at least 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, broad outcome variability persists on measures of speech recognition, [1][2][3] some of which can be attributed to patient-related factors (eg, residual hearing) 4 and spectrotemporal resolution. 3,5,6 Additionally, neurocognitive functions, such as verbal learning, working memory, and inhibitory control, relate to outcomes. 3,7,8 Evidence for the efficacy of auditory rehabilitation on both auditory processing and neurocognitive functions continues to grow.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for the spectral ripple test's popularity is that spectral ripple thresholds have been demonstrated to correlate with speech perception tests, including word, consonant, and vowel recognition (Henry et al 2005), and speech recognition in 111 noise (Won et al 2007;Lawler et al 2017; although note that Anderson et al 2011, did not observe robust correlations with any speech perception measure). Higher (better) 113 ripple discrimination thresholds are also associated with better musical perception (Won et al 2010).…”
mentioning
confidence: 99%